2018
DOI: 10.1007/s00259-018-3937-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-early response assessment in lymphoma treatment: [18F]FDG PET/MR captures changes in glucose metabolism and cell density within the first 72 hours of treatment

Abstract: PurposeTo determine whether, in patients with Hodgkin lymphoma (HL) or non-Hodgkin lymphoma (NHL), [18F]FDG PET/MR can capture treatment effects within the first week after treatment initiation, and whether changes in glucose metabolism and cell density occur simultaneously.MethodsPatients with histologically proven HL or NHL were included in this prospective IRB-approved study. Patients underwent [18F]FDG PET/MR before, and then 48–72 h after (follow-up 1, FU-1) and 1 week after (FU-2) initiation of the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…Our findings partly support this hypothesis; all tumors decreased in size during therapy (independent of later response), but these changes were very small and occurred later than observed changes in SUV and ADC. This is also confirmed by another recent study applying FDG-PET/MR for very early response evaluation [41].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings partly support this hypothesis; all tumors decreased in size during therapy (independent of later response), but these changes were very small and occurred later than observed changes in SUV and ADC. This is also confirmed by another recent study applying FDG-PET/MR for very early response evaluation [41].…”
Section: Discussionsupporting
confidence: 81%
“…In 1999 European Organization for Research and Treatment of Cancer (EORTC) published guidelines for measurement of clinical and subclinical tumor response using FDG-PET [34]. In 2009 a new set of guidelines Positron Emission Tomography Response Criteria in Solid Tumors (PERCIST) [29,35] was proposed and even though the acceptance of these criteria have been quite slow, recent publications support the use of PERCIST over the more simple EORTC criteria [36,37,38,39,40,41,42,43,44,45,46,47,48,49]. This study applied, for the first time in a PET/MR setting, PERCIST measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid PET/MR has been introduced into the clinical application setting since 2011. Studies on the feasibility and potential applications of PET/MR imaging have been reported soon after that, and oncology was one of the hot topic (4)(5)(6)(7)(8). Because multiparametric PET/MR imaging can provide many biomarkers of the studied diseases non-invasively, it was widely used in oncological research, especially for the tumor diagnosis, treatment planning, surveillance, and follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical use of functional imaging techniques has been limited in the assessment of immunotherapy response. The value of MRI diffusion has been demonstrated in lymphoma patients [ 74 , 75 , 83 , 84 ], and CT perfusion has been applied for response assessment of interferon 1-treated metastatic renal cancer and carcinoid tumors [ 85 , 86 ].Functional imaging techniques might also facilitate the differentiation between tumors and inflammatory sites in glioblastoma patients treated with dendritic cell immunotherapy [ 87 ].…”
Section: Functional and Molecular Imaging Advances For Immunotherapy mentioning
confidence: 99%